Prices for Poverty Analysis in Africa - Gaddis, Isis (World Bank, Washington, DC, 2016)
Measuring poverty requires adjusting nominal consumption (or income) into a real value of consumption, across geographic areas and over time. To this end, data on consumer prices are used to construct a price index. There are a range of approaches to do this, from using the consumer price index, to survey-based unit values, which differ in the underlying sources of price data and methodologies for indexing. These different approaches can have large impacts on poverty measures and trends. Surprisingly little attention has been focused on this topic. This study reviews a range of issues and the evidence on how prices matter for measuring poverty, particularly in Africa. It draws on a wide literature, much from developed countries, and offers suggestions for future work in this area.